THE RELATIONSHIP BETWEEN MANAGEMENT EDUCATION AND LACTATION MASSAGE WITH MATERNAL BEHAVIOR IN BREASTFEEDING - Aulya Pretty Aryanda; Atikah Uzri; Ester Juniati Halawa; Feniria Zega; Debi Novita Siregar (PT. Radja Intercontinental Publishing, 2025)
Supplying only breast milk (ASI) in the first six months of a child's life plays a crucial role in promoting healthy development and strengthening the immune system. Nonetheless, the rate of exclusive breastfeeding in Indonesia continues to fall short of the desired target. Several contributing factors include mothers' lack of knowledge, attitudes, and skills in lactation management. One effort that can increase breastfeeding success is education about lactation management and the application of lactation massage. This study aims to identify the correlation between management education and lactation massage with maternal behavior in providing breast milk. This study uses a one-group pretest-posttest quasi-experimental design and a quantitative methodology. Using the complete sampling approach, the sample size was 30 people, and the population was made up of breastfeeding mothers. A questionnaire that evaluated moms' knowledge, attitudes, and behaviors both before and after receiving education served as the research tool. The Wilcoxon signed rank test has been used in data analysis to find significant differences between the outcomes before and after the intervention. The research results showed that before education, the majority of mothers had sufficient knowledge (50%), negative attitudes (56.7% disagreed), and balanced actions between doing and not doing lactation massage (50% each). After education, almost all respondents had good knowledge (96.7%), positive attitudes (43.3% strongly agreed), and all respondents (100%) performed lactation massage. The Wilcoxon test produced ap value = 0.000 (p < 0.05) which indicates a significant difference between before and after the intervention.